The shared numerical representation for action and perception develops independently from vision. (August 2020) - Togoli, Irene; Crollen, Virginie; Arrighi, Roberto; Collignon, Olivier
Abstract: Humans share with other animals a number sense, a system allowing a rapid and approximate estimate of the number of items in a scene. Recently, it has been shown that numerosity is shared between action and perception as the number of repetitions of self-produced actions affects the perceived numerosity of subsequent visual stimuli presented around the area where actions occurred. Here we investigate whether this interplay between action and perception for numerosity depends on visual input and visual experience. We measured the effects of adaptation to motor routines (finger tapping) on numerical estimates of auditory sequences in sighted and congenitally blind people. In both groups, our results show a consistent adaptation effect with relative under- or over-estimation of perceived auditory numerosity following rapid or slow tapping adaptation, respectively. Moreover, adaptation occurred around the tapping area irrespective of the hand posture (crossed or uncrossed hands), indicating that motor adaptation was coded using external (not hand-centred) coordinates in both groups. Overall, these results support the existence of a generalized interaction between action and perception for numerosity that occurs in external space and manifests independently of visual input or even visual experience.